Improving the SDGs through Green HRM, Green Training, and Innovative Leadership - Bambang Nurakhim; Yuni Pratikno; Dewi Ulfa Arini; Amin Lestari; Yuniria Zendrato (Goodwood Publishing, 2025)
Purpose: To analyze the influence of Green Human Resource Management (Green HRM), Green Training, and Innovative Leadership on the achievement of the SDGs. The theories used include the Resource-Based View and organizational sustainability concepts. Research Methodology: Employed a quantitative approach with data collection through questionnaires distributed to 150 respondents from various service subsectors. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. Results: Indicate that: 1) Green HRM has a positive and significant effect on SDGs achievement; 2) Green Training has a positive and significant effect on SDGs achievement; 3) Innovative Leadership has a positive and significant effect on SDGs achievement; 4) Simultaneously, the three variables explain 48.3% of the variance in SDGs achievement. Conclusions: Suggest that Green HRM plays an important and positive role in supporting the achievement of SDGs. Green Training also significantly contributes to enhancing organizational capacity to reach these goals. Additionally, Innovative Leadership is found to positively influence SDGs achievement. Limitations: Implications highlight the importance of integrating green practices in HR management, sustainability training, and innovative leadership to support SDGs agenda at the corporate level Contribution: It is suggested that service companies further strengthen the implementation of Green HRM, Green Training, and Innovative Leadership to achieve the SDGs.